Team Marvel with 1st place trophy (first place) and prototype firefighter uniform - Eisele, John, photographer (Colorado State University. Libraries, 2016)
Team Marvel.
The 2016 Fairmount Fire Rescue Fire Department Uniform Design was held at the Gifford Building, Colorado State University.
AM375.
SP2016 AM375 Firefighter Uniform Redesign.
Keywords: Fire departments -- Uniforms -- Design -- Awards; Fashion design -- Awards